Development of Renewable Energy Potential in Kuwait - Naser, A. N. Muhaisen; Musse, Mohamud Ahmed; Sheroz, Khan; Mohamed, H. Habaebi; Nabil, A. Ahmed; Atika, Arshad (IEEE, 2016)
This paper is aimed at proposing an effective solution to enhance continuous power availability and to reduce the peak load demand in Kuwait electric grid system. The peak demand is made up from solar renewable energy sources. The potential of renewable energy as power generation sources in Kuwait has been studied and solar energy potential has been analyzed. In the pursuit of proposing a system based on a hybrid of solar and wind, this paper only discusses the solar energy part. In this paper, solar energy system performance has been simulated using PSIM software in order to examine the real justification of utilizing it as an alternative solution to Kuwait electricity demand during peak hours of a hot summer day.